Bioequivalence Studies of Two Formulations of Famciclovir Tablets by HPLC Method - SUBRAHMANYAM, K.V.; MOHANRAJ, P.; SANDHYARANI, P.; SARAVANAN, V.S.; GOPAL, N. (Asian Journal of Chemistry, 2010)
The objective was to compare the bioavailability of two tablet dosage forms of famciclovir in rabbits. Serum levels of famciclovir was determined by using high performance liquid chromatography. The pharmacokinetic parameters were estimated following the oral administration of a single dose (250 mg) tablet of the drug to 12 healthy rabbits. All rabbits received a single oral dose of the medication in a two period, two way cross-over design. The difference between the formulations were statically insignificant. In all the cases the relative bioavailability of the test was found to be in the range of 83-105 %. No adverse reactions were observed during the entire study. The test formulation manufactured by Cipla Lab., was found to be bioequivalent to the reference product.